A bioethical examination of the use of human emotions as a film marketing tool on short video platforms: normative morality applicable to film marketing matrix - Zhang, Huiyi; Zang, Zheng (Acta Bioethica, 2022)
The marketing matrix on a short video platform is an intriguing research topic. It is a novel film marketing strategyon the short video platform that successfully stimulates the audience’s emotion in the film marketing process, but it must alsobe ethically tested.To address this desire, we examine the problem using normative ethics (consequentialism, deontology, andvirtue ethics). The marketing matrix will be addressed within the framework of philosophical ethics, whose emotional marketingcan be tested, in what follows, through reviews of literature and content analysis. First and foremost, a matrix standpoint willbe adopted in order to provide a preliminary conceptualization along with its emotional techniques of the marketing matrix;then, the marketing matrix will be addressed within the framework of philosophical ethics, whose emotional marketing can betested. In the future, when creating a moral marketing matrix, the author proposes that numerous ethical concepts be taken intoaccount comprehensively.